2002
DOI: 10.1034/j.1600-6143.2002.20707.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Crystal Deposits in Abdominal Organs Following Perfusion with Defrosted University of Wisconsin Solutions

Abstract: Previous studies reported on both visible and invisible particles in University of Wisconsin (UW) solutions. Those particles originated from components of the bags. In recent clinical observations we noticed macroscopically visible, indissoluble particles in UW bags reaching subzero temperatures during transportation of organs and preservation solutions. In an experimental model we examined whether those particles could be detected following perfusion of abdominal organs with established perfusion solutions. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
0
22
2
4
Order By: Relevance
“…In contrast to our findings of two prominent masses at 358 and 504, Walcher et al identified the source of particles as lipid salts of stearic (mass 284.5) and palmitic acids (mass 256.4) derived from the plastic bags containing the UW solution [3]. Tullius et al also found crystalline particles of composition other than palmitic and stearic acid in UW solution [5]. The particles they isolated featured multiple masses by mass spectrometry, with only adenosine (mass 267) being identified (A. Lun, personal communication).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast to our findings of two prominent masses at 358 and 504, Walcher et al identified the source of particles as lipid salts of stearic (mass 284.5) and palmitic acids (mass 256.4) derived from the plastic bags containing the UW solution [3]. Tullius et al also found crystalline particles of composition other than palmitic and stearic acid in UW solution [5]. The particles they isolated featured multiple masses by mass spectrometry, with only adenosine (mass 267) being identified (A. Lun, personal communication).…”
Section: Discussioncontrasting
confidence: 52%
“…A recent report by Tullius et al noted that storage temperatures less than/equal to -3 f 0.5 "C exacerbated particle generation in UW solution [5]. Under these conditions, insoluble, visible particles were substantial, with a yield estimated to be 700 mg/l of UW solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, considerando que la vía biliar es irrigada exclusivamente desde la arteria, aquellas soluciones que lleguen fácilmente al lecho capilar distal, tendrían una ventaja sobre el daño isquémico de ésta. Se ha observado que a temperaturas sobre 4ºC, UW puede producir cristales de adenosina, los que ocluirían las ramas distales arteriales que irrigan el árbol biliar 24 . Esto no ocurre con HTK, que puede ser conservada entre 4 y 15ºC 24 .…”
Section: Discussionunclassified
“…However, it has disadvantages due to its high viscosity, reducing the capacity of penetration into the microcirculation and bile ducts and particularly its high cost 18,20 .…”
Section: Introductionmentioning
confidence: 99%